STRATEGI KOMUNIKASI PEMASARAN PADEPOKAN SENI TARI PARIKESIT DALAM MEMPERKENALKAN TARIAN TRADISIONAL GAMBYONG DAERAH JAWA TENGAH - Febiana Jeanne Kristianingrum; Susanto Susanto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Abstract A true heritage is a legacy given by our ancestors that we should maintain or preserve so that the culture can be known to many people. Many efforts can be done to preserve Indonesian culture to preserve local dances. One of them is by making a container or dance studio. Padepokan Parikesit Dance is a place that is made as a dance studio, one of the aims of its activities is to preserve Indonesian culture, especially traditional dance and music and puppets in the hope that it can create creative young people and love for local art. Using qualitative methods with constructivist paradigms.